Practicality and Effectiveness of STEM-R Electronic Modules in Improving Students' Mastery of Material on Environmental Conservation - Wawan Darmawan; Djohar Maknun; Mujib Ubaidillah (Scientiae Educatia: Jurnal Pendidikan Sains, 2023)
The development of internet-integrated teaching materials is important in meeting the demands of education in the era of globalization, which allows students to access information quickly and keep it up-to-date. In addition, integrating various branches of science in teaching materials can enrich students' knowledge, improve critical thinking skills, and prepare them to face global challenges. This study aims to analyze the feasibility of STEM-based electronic modules on environmental conservation materials, the practicality of STEM-R-based electronic modules on environmental conservation materials, and the effectiveness of STEM-R-based electronic modules in improving mastery of environmental conservation materials. This study uses the Research and Development (R&D) method with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study involved media experts, material experts, biology teachers, and students, while the object of the study was the STEM-R-based electronic module. Data collection techniques used include Validation sheets to assess the feasibility of the module, practicality questionnaires to evaluate the practicality of the module, and test instruments to measure the module's effectiveness in improving mastery of environmental conservation material concepts. The study results showed that the developed electronic module was declared feasible with an overall Content Validity Ratio (CVR) and Coefficient Validity Index (CVI) value of 1, the developed electronic module was declared very practical with a practicality percentage of 96.17%, and the developed electronic module obtained an N-Gain value of 0.64. The STEM-R-based electronic module is categorized as moderately effective in improving students' mastery of environmental conservation material.